2017
DOI: 10.1186/s12864-017-3770-y
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis reveals technical artifacts in TCGA germline variant calls

Abstract: BackgroundCancer research to date has largely focused on somatically acquired genetic aberrations. In contrast, the degree to which germline, or inherited, variation contributes to tumorigenesis remains unclear, possibly due to a lack of accessible germline variant data. Here we called germline variants on 9618 cases from The Cancer Genome Atlas (TCGA) database representing 31 cancer types.ResultsWe identified batch effects affecting loss of function (LOF) variant calls that can be traced back to differences i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…8072, Integrated analysis of germline and somatic perturbation as it relates to tumor phenotypes). Whole exome (WXS) germline variant calls from 8542 individuals were obtained using GATK v3.5 as described previously [ 20 ]. The samples prepared using whole genome amplification (WGA) were excluded from the analysis due to previous identification of technical artifacts in both somatic and germline variant calls in WGA samples [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8072, Integrated analysis of germline and somatic perturbation as it relates to tumor phenotypes). Whole exome (WXS) germline variant calls from 8542 individuals were obtained using GATK v3.5 as described previously [ 20 ]. The samples prepared using whole genome amplification (WGA) were excluded from the analysis due to previous identification of technical artifacts in both somatic and germline variant calls in WGA samples [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whole exome (WXS) germline variant calls from 8542 individuals were obtained using GATK v3.5 as described previously [ 20 ]. The samples prepared using whole genome amplification (WGA) were excluded from the analysis due to previous identification of technical artifacts in both somatic and germline variant calls in WGA samples [ 20 , 21 ]. Somatic mutation calls obtained using MuTect2 were downloaded from GDC as Mutation Annotation Format (MAF) files [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…As genomic analysis becomes more common in clinical practice, it is critical for the scientific community to understand not only how to accurately model mutations and experimental error but also how to choose an appropriate variant caller and how various aspects of clinical and laboratory workflow can affect the performance of the algorithms they use [ 27 ]. The goal of this review is to discuss known experimental features, such as sample preparation, library preparation, and sequencing alongside diverse biological and clinical features and evaluate their effect on variant caller selection and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, this broad scope makes it more susceptible to measurement errors. For example, Buckley et al found technical artifacts in TCGA germline samples due to whole chromosome amplification resulting in spurious indel calls [ 5 ].…”
Section: Introductionmentioning
confidence: 99%